2021
DOI: 10.1186/s40949-021-00061-3
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and congenital heart disease: perioperative planning and management

Abstract: Approximately 50% of newborns with Down syndrome have congenital heart disease. Non-cardiac comorbidities may also be present. Many of the principles and strategies of perioperative evaluation and management for patients with congenital heart disease apply to those with Down syndrome. Nevertheless, careful planning for cardiac surgery is required, evaluating for both cardiac and noncardiac disease, with careful consideration of the risk for pulmonary hypertension. In this manuscript, for children with Down syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 126 publications
(189 reference statements)
0
21
0
1
Order By: Relevance
“…It is suggested by studies that the most common lesion observed in children with DS having CHD is variable according to different geographic regions in the world [ 9 , 10 ]. Therefore, it is important to know the profile and association of CHD in DS for a given geographic area for the planning of management like intervention, surgical management and medical follow-up keeping in view the high risk of pulmonary vascular disease in these patients [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested by studies that the most common lesion observed in children with DS having CHD is variable according to different geographic regions in the world [ 9 , 10 ]. Therefore, it is important to know the profile and association of CHD in DS for a given geographic area for the planning of management like intervention, surgical management and medical follow-up keeping in view the high risk of pulmonary vascular disease in these patients [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cardiac problems, chromosomal abnormalities also may cause developmental delays and slow postoperative recovery. Dennis noted that underlying comorbidities with Down syndrome might increase postoperative complications and length of stay [Delany 2021]. Longer ventilator use may reflect worse postoperative lung conditions in these patients, requiring more extended hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the assessment reveals no changes or symptoms of cervical instability, the anesthesia professional should consider avoiding neck flexion or extension during laryngoscopy and using an in‐line neck stabilizer or collar. Also, the anesthesia professional should consider the use of fiberoptic 9 or video‐assisted 10 laryngoscopy. Perioperative nurses should be prepared to assist with airway management if needed.…”
Section: Comorbidities Associated With Dsmentioning
confidence: 99%
“…The nurse should ensure that the severity of the abnormality, the status of repair, and the presence of any residual lesions have been thoroughly assessed and documented before surgery. Because children with DS have an increased risk of developing bradycardia during anesthesia induction, anticholinergic agents (eg, atropine) should be readily available during the procedure 9 …”
Section: Comorbidities Associated With Dsmentioning
confidence: 99%
See 1 more Smart Citation